(untitled) (Experimental biology, 2015)
Extremely increased immunosuppressive activity of myeloid derived suppressor cells (MDSC), a heterogeneous population of early myeloid precursors, is one of the main reasons for failure of the immune system, which includes natural killer cells, macrophages, dendritic cells and cytotoxic T lymphocytes, to inhibit tumor growth on the late stage of its development. MDSC suppress antitumor immunity and as a result significantly decrease the positive effect of anticancer immunotherapy. In this regard development of new approaches to effective elimination of MDSC from organisms that bear a growing tumor is an urgent problem of modern cancer immunology. Utilization of alphafetoprotein (AFP) as a vector molecule composed of cytotoxic conjugate, which is specifically recognized by MDSC receptors, for the purpose of their elimination and hereby activation of antitumor immunity is proposed.